Sphenoidal pneumosinus dilatans due to anterior skull base meningiomas – CT and MRI aspects: Report of two new cases and literature review. Issue 4 (August 2016) - Scuotto, Assunta; Saracino, Dario; Rotondo, Michele; Izzo, Andrea; Urraro, Fabrizio; Cappabianca, Salvatore; Sampaolo, Simone
We report on two patients disclosing a pneumosinus dilatans (PSD) and an anterior skull base meningioma. Our findings, together with those from the pertinent literature, support the thought that this infrequent anomaly of paranasal sinuses is a useful clue to suspect a concomitant meningioma. Moreover, hypotheses concerning the pathophysiology of PSD are discussed.